LONG-TERM SERVICES AND SUPPORTS USE (LTSS): ADAPTING A CONCEPTUAL MODEL TO INCLUDE OLDER ADULTS RECEIVING LTSS. (11th November 2018) - Travers, J; Hirschman, K; Naylor, M
Abstract: Andersen's Expanded Behavioral Model of Health Services Use describes the psychosocial, enabling, and need characteristics associated with long-term services and supports (LTSS) use. Testing of this model, however, has only focused on the intent to use such services. In light of an increasing minority older adult population utilizing LTSS, the ability to conceptualize determinants of actual use across diverse racial groups is critical. We present results from in-person interviews of older adults describing reasons for actual use of LTSS. From April 2006 to December 2010, 464 older adults (>= 60 years) new to LTSS (51% white; 34% African-American; 14% other race/s) were enrolled in the Health-Related Quality of Life: Elders in Long-term Care study (R01AG02552). A single open-ended item asking "Can you tell me why you moved to [Name of Facility]?" was analyzed using directed, classical, and conventional content analyses. African-Americans and whites differed in their level of participation in the choice to use LTSS with 44% African-Americans reporting others made the decision on their behalf compared to 25% whites. Reports of LTSS use to avoid burdening one's family were greater among whites (6%) than African-Americans (1%). Four new constructs emerged under the psychosocial and enabling factors--losses and changes, tangible support, capability to provide support, accessibility of informal support- will be discussed. Our analyses reveal racial differences in factors influencing actual LTSS use. Findings around decision-making and burden along with other constructs may enhance our understanding of determinants that potentially require targeted interventions specific to racial groups.